Une source d’argumentation dans l’appel de grand criminel à la fin du xviie siècle : les lettres de cassation présentées au parlement de Toulouse - Isabelle Arnal-Corthier (Clio@Themis)
In the last three decades of the seven,teenth century, although a recent criminal ordinance stipulated that the only formality required in the case of an appeal concerning a grand criminel was reduced to a hearing of the accused, in some rare cases in the Parliament of Toulouse, the accused found a way of presenting a more elaborate defence, involving the participation of lawyers. Indeed, producing a document called “Lettres royaux pour obtenir cassation” (Royal Letters for cassation) was not excluded during the interrogation. This had the effect of “having received the trial in written form”. It was then an attorney (and sometimes an advocate) who developed the argument for cassation of the proceedings for the applicant in the first instance. In order to understand this procedure, we will analyze the typologies of the arguments proposed by the legal professionals, both in accordance with the royal ordinance of 1670 and otherwise.